2021
DOI: 10.1007/s12134-020-00799-6
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Mobility in a Polarized World: Questioning the Pertinence of the “Climate Refugee” Label for Pacific Islanders

Abstract: This note offers thoughts on the conceptual and empirical debate surrounding the "climate refugees" label, created as a theoretical category of migrants to reflect the plight of environmentally vulnerable communities. This note challenges this status on conceptual terms. First, we investigate its academic foundations and contend that it fails to portray the complexities of choice, agency, and causality in climate-induced mobility. We then parallel this concept with narratives on traditional asylum seekers to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
4
0
2
Order By: Relevance
“…In practice, the use of the climate refugee frame often manifests as the unilateral forging of narratives (often by NGOs and policymakers) for displaced people or people at risk of displacement. Such narratives do not converge with the situated concerns and understandings articulated by the very people they are said to describe (Farbotko and Lazrus, 2012;Munoz, 2021). This raises serious questions about how the empty, symbolic invocation of embodied experiences of displacement in the context of climate change, environmental degradation, and disaster can be made to function as components of wider narratives constructed from without.…”
Section: A Useful Concept? Analytical Evaluation Of the Notion Of Cli...mentioning
confidence: 98%
See 1 more Smart Citation
“…In practice, the use of the climate refugee frame often manifests as the unilateral forging of narratives (often by NGOs and policymakers) for displaced people or people at risk of displacement. Such narratives do not converge with the situated concerns and understandings articulated by the very people they are said to describe (Farbotko and Lazrus, 2012;Munoz, 2021). This raises serious questions about how the empty, symbolic invocation of embodied experiences of displacement in the context of climate change, environmental degradation, and disaster can be made to function as components of wider narratives constructed from without.…”
Section: A Useful Concept? Analytical Evaluation Of the Notion Of Cli...mentioning
confidence: 98%
“…Despite having little legal pertinence on an international scale, the term has been used by a range of media outlets (Dinshaw, 2015; Gilbert, 2009; Teffer, 2015; Carrington, 2016), activists and non-governmental organizations (NGOs; Friends of the Earth, 2017; Vong, 2017; Climate Refugees, 2021; Environmental Justice Foundation, 2021), politicians (Juncker, 2015; Castro, 2020), and scholars (Lister, 2014; Faber and Schlegel, 2017; Salem and Rosencranz, 2020) while being actively rejected by others (Farbotko and Lazrus, 2012; Munoz, 2021). The debates around climate refugees pose challenges in that there remains a serious lack of consensus both on what exactly is meant by the notion of climate refugee (Bates, 2002; Biermann and Boas, 2010; Brown, 2008; Dun and Gemenne, 2008) and the basis on which it should or should not be used (Kniveton et al, 2008; Munoz, 2021; Piguet, 2010). These debates attest to the tangible ways in which the realms of the linguistic, legal, and material triangulate.…”
Section: Definitional Difficulties: What Is the Meaning Of ‘Climate R...mentioning
confidence: 99%
“…There is no internationally defined terminology for individuals migrating for environmental reasons. The concept "climate refugee" is difficult to institutionalize at the international level since it would require challenging dominant conceptions of humanitarian and environmental distress, or the concept "displaced person" generally alludes to "internationally displaced persons" (Munoz, 2021). Yet, at the most generic level, environmental migrant refers to "persons or groups of persons who, for compelling reasons of sudden or progressive changes in the environment that adversely affect their lives or living conditions, are obliged to leave their habitual homes or choose to do so, either temporarily or permanently, and who move either within their country or abroad" (IOM, 2007: para.…”
Section: Environmental (Non) Migrationmentioning
confidence: 99%
“…8 Reputable United Nations organizations, in turn citing other United Nations organizations, reproduce an oft-cited estimated range of 25 million to one billion climate migrants by 2050, with no reference to the original study that produced the figures. Some academic works cite non-academic sources of information on mass climate migration, such as news articles, 9 while the news media publishes its own accounts of international climate change migration, eschewing citation of scientific studies: the IPCC AR6 noted that ''media reports and other studies in recent years suggest that climate change has driven large numbers of migrants to the US from Central America and to Europe from the Middle East and Africa, but empirical studies were not identified.'' 6 Myers' rejected models have recently been problematically applauded for ''putting the issue [of climate migration] on the global agenda.''…”
Section: The Specter Of Mass Climate Migrationmentioning
confidence: 99%